Reduction of Modal Vibration Effect in Load Identification of a Train Bogie Frame. Issue 2 (March 2021) - Ma, Shuang; Sun, Shouguang; Jin, Xincan; Wang, Ning; Wang, Binjie
Abstract: In order to identify the external applied load on train bogie frame, the load response measured by sensor, e.g. strain gauges, is used in engineering practice. However, it is difficult to model the load-response correlation precisely since the bogie frame system characteristic is complicated, especially, it contains many modal vibration effects. The commonly used linear load-response correlation assumption thus deviates from the truth especially at resonant frequencies. A new approach to reduce the modal vibration effect from the load response based on single degree of freedom assumption is proposed in this article. The approach is applied on real measurement of Beijing Subway train bogie frame and the reduction performance is verified.